Reconfigurable Computing: Architectures, Tools and Applications 6th International Symposium, ARC 2010, Bangkok, Thailand, March 17-19, 2010, Proceedings - Sirisuk, Phaophak; Morgan, Fearghal; El-Ghazawi, Tarek; Amano, Hideharu (Theoretical Computer Science and General Issues, 2010)
Recon?gurable computing (RC) systems have generated considerable interest in the embedded and high-performance computing communities over the past two decades, with ?eld programmable gate arrays (FPGAs) as the leading techn- ogy at the helm of innovation in this discipline. Achieving orders of magnitude performance and power improvements using FPGAs over traditional microp- cessorsis not uncommon for well-suitedapplications. But even with two decades of research and technological advances, FPGA design still presents a subst- tial challenge and often necessitates hardware design expertise to exploit its true potential. Although the challenges to address the design productivity - sues are steep, the promise and the potential of the RC technology in terms of performance, power, size, and versatility continue to attract application design engineers and RC researchers alike. The International Symposium on Applied Recon?gurable Computing (ARC) aims to bring together researchers and practitioners of RC systems with an emphasis on practical applications and design methodologies of this promising technology. This year's ARC symposium (The sixth ARC symposium) was held in Bangkok, Thailand during March 17-19, 2010, and attracted papers in three primary focus areas:RC applications, RC architectures, and RC design meth- ologies.